Minat Belajar dan Kemampuan Pemecahan Masalah Matematika Siswa melalui Model CPS di Kelas IX - Mami Suriarti; Isnaniah Isnaniah (Journal on Education, 2023)
The research aims to determine students' interest in learning and mathematical abilities by applying the Creative Problem Solving (CPS) model in class IX SMPN 1 Koto Balingka. This type of research is pre-experimental with the research design The Static Group Comparison Design. The sample in this study were students in class IX 1 as the experimental class and students in class IX 4 as the control class, amounting to 22 students each. The instruments used were a questionnaire of students' interest in learning and a test of mathematical problem solving abilities in the form of a description test. Questionnaire data analysis techniques were processed using percentage calculations while the problem solving ability test was processed by t-test. Based on the results of data analysis of students' interest in learning questionnaires, it was obtained that the percentage of 65.44% was classified as high criteria and tests of students' mathematical problem solving abilities were calculated using the t-test obtained t_count = 4.24 and t_table = 1.68 because t_count > t_table means H_O was rejected, while using the Minitab software obtained P-value = 0.000, α = 0.05 and P-value <α. So, it can be concluded that students' interest in learning mathematics by following the CPS model is high and the math problem solving abilities of students using the CPS model are better than conventional learning in class IX of SMP Negeri 1 Koto Balingka, West Pasaman Regency, 2022/2023 academic year.